Desenvolvimento de blendas ternárias com poli (álcool vinílico) e policaprolactona como estratégia de redução da sensibilidade à água de filmes de amido termoplástico - Nicolino, Marcos Vinícius Batista (2025)
Polymeric solid waste management remains inefficient in mitigating the environmental consequences of improper disposal, motivating the development of biodegradable materials such as thermoplastic starch (TPS), derived from renewable sources. However, TPS is moisture-sensitive and shows tensile strength and elongation at break values about three times lower than those of low-density polyethylene (LDPE), requiring modifications to achieve comparable performance. In this work, TPS blends, with and without citric acid, were formulated with up to 20 wt% poly(ε-caprolactone) (PCL) and up to 30 wt% poly(vinyl alcohol) (PVOH) to produce flexible films. The strategy was based on the hypothesis that combining a polar polymer, a nonpolar polymer, and a modifying agent would direct the morphological development of the ternary system, enabling control over water interaction kinetics while preserving biodegradability. The study comprised: (i) TPS development from different vegetal sources and citric acid concentrations; (ii) definition of the mixing protocol for TPS/PVOH binary blends; and (iii) thermodynamic prediction of ternary blend morphology by correlating surface tensions with observed structures. A strong interaction between TPS and PVOH phases was observed, whereas PCL formed polydisperse domains and migrated toward the film surface. The resulting morphologies directly influenced film properties, leading to tensile strength and elongation at break values up to 15 times higher than neat TPS and wettability comparable to pure PCL with only 20 wt% PCL. Although PCL reduced soil deterioration, it did not inhibit biodegradation. The resulting TPS/PVOH/PCL blends may enable applications requiring a balance between stability in use and biodegradability, such as controlled-release systems and packaging films.